Modelling and analysis of a renewable energy-driven climate-controlled sustainable greenhouse for hot and arid climates - Omer Abedrabboh (17346847) (2022)
Population growth and improved living standards led to increased demand for food and crops, of which cultivation is heavily affected by average ambient temperature increase resulting from global warming. Hot and arid climate regions with high average summer temperatures suffer further as agricultural greenhouse indoor temperature reaches levels much higher than the ambient, causing severe dehydration and eventual death of crops. This research proposes an innovative, resilient and sustainable integrated greenhouse system to control greenhouse indoor climate within the cultivation range. This system consists of concentrating photovoltaic thermal system utilizing nucleate boiling heat transfer, thermal energy storage based on phase change material, lithium bromide absorption cooling system and dehumidifier, borehole ground heat exchanger, and spectrum selective roof for a greenhouse. The system is driven by renewable energy sources: Solar irradiation, ambient air, and geothermal cooling to provide electricity, space cooling, air-conditioning, and irrigation water. A comprehensive thermodynamic analysis of the sustainable integrated greenhouse system was done to obtain the energy and exergy efficiencies of the subsystems and overall system. The analysis shows overall energy and exergy efficiencies of 43.36 % and 19.19 %, respectively. Compared to the conventional greenhouse roof, the spectrum selective roof efficiently reduced the maximum cooling load by 29.2 %. Under the investigated hot and arid climate conditions, the system produced 33.28 kW of cooling, 29.3 kW of electricity, 8.36 L/h of dehumidified irrigation water, and 250 m3/h of dry ventilation air. An economic analysis based on the life cycle cost was executed to determine the economic feasibility of the integrated system. The recorded levelized cost of cooling, electricity, and water are 0.021 USD/kWhc, 0.0366 USD/kWhele, and 8.8 USD/m3, respectively, presenting a cost-competitive standalone integrated system. Other Information Published in: Energy Conversion and Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.enconman.2022.116412